Pengaruh Penggunaan Media Pembelajaran Interaktif Mentimeter Terhadap Hasil Belajar Pendidikan Agama Islam - Putri, Riry Mahesa; Nurjanah, Nurjanah (Prodi Pendidikan Keagamaan Islam, 2025)
This study aims to determine the effect of using Mentimeter interactive learning media on the learning outcomes of Islamic Religious Education (PAI) of grade IX students at SMP N 26 Padang. The background of this study is based on the low learning outcomes of students in the subject of PAI, which is partly caused by the limited use of varied and interactive learning media. This study uses a quantitative approach with a quasi-experimental method using the Posttest-Only Control Group Design. The research sample consisted of two classes, namely the experimental class using Mentimeter media and the control class using the conventional lecture method. Data were collected through multiple-choice learning outcome tests. The results showed that the use of Mentimeter interactive media had a significant effect on improving student learning outcomes. Based on the t-test analysis, there was a significant difference between the learning outcomes of students using Mentimeter and students who learned using conventional methods. Thus, the use of Mentimeter interactive learning media can be an effective alternative in improving learning outcomes of Islamic Religious Education in junior high schools.